“The Turk” Motif in Rumi’s Poems - Davoud Sparham (Şarkiyat Mecmuası)
Like other poets, Rumi used various symbols to effectively express his thoughts, beliefs and feelings. Turk as a word and literary symbol is one of the motifs that Rumi had much to do with due to his presence in the land of the Turks (Eastern Rome) and the fact that his beloved teacher, (Shams Tabrizi) was also Turk. By performing a complete review of Rumi’s works, this article precisely elaborates on the scope of semantic and literary usage (symbolic and non-symbolic) of the Turk motif as well as the interpretations and images Rumi presented by referencing this motif. The most important literary use of “ the Turk motif” in Rumi’s poems was to establish artistic and spiritual/semantic contrasts between Turks and Hindus, Tajiks, Armenians, Romans, Bulgarians, Arabs, Kurds or Zanzibaris. In addition to this, Rumi also used the Turkish motif to express special symbolic features such as; the beloved, beauty and flirtation, strength and sharpness, and plunder and desertion, as well as metaphors such as the moon and the sun. The diversity of Turkic peoples in Rumi’s language is another point to which this article pays attention. Rumi wrote about the Khatai Turk, Turkestan Turk, Targhir Turk, Turkman Turk, and Tabrizi Turk. Rumi exhibited a unity of the existential and the intuitive and thus used his singleminded approach to create the most beautiful and magnificent spiritual and meaningful expression of unity in the Sufi multiplicity by taking advantage of the diversity and formal plurality of nations and languages.